Economic and Political Aspects of the Serbia — EAEU Free Trade Area - A. V. Toropygin (Евразийская интеграция: экономика, право, политика, 2021)
The article is devoted to the analysis of the Serbia — EAEU relations development through the prism of the Agreement on the Free Trade Area (FTA) — between the integration association and the separate economy / country. The purpose of this study is to identify the prospects of the FTA taking into account Serbia’s desire to integrate into the European Union. The author come to the conclusion that intensive interaction, primarily between Serbia and Russia through the FTA between Serbia and the EAEU, is explained, on the one hand, by Serbia’s multi-vector foreign policy, and, on the other hand, by Russia’s attentive attitude to the course of the conflict over Kosovo. Russia has economic interests in this region, as well as the region is people-related value for Russia within which it has used and will intensively utilize of soft power mechanisms.